Analysis of birth outcomes with incidence of hepatitis B in pregnant women - Handayani, Lisda; Anisa, Fadhiyah Noor; Palimbo, Adriana; Suhartati, Susanti; Raudah, Normila; Ibrahim (Ananda - Health & Education Foundation, 2024)
Background: Hepatitis B in Indonesia is highest endemic, second mostly in the South East Asian Region. Hepatitis is generally rare in pregnant women. However, the most common sign is gestational jaundice, which is the cause of viral hepatitis. A total of 50,744 pregnant women will be positive for hepatitis B in 2022. Of this number, there will be 35,757 babies born to women who are positive for hepatitis B. The magnitude of this problem will certainly have a huge impact on public health problems and productivity. Objective: to know birth outcomes with incidence of hepatitis B in pregnant women. Method: Type of analytical quantitative research, case-control design. The total data sample was 60 pregnant women, including 30 hepatitis B cases and 30 non-hepatitis B controls. Secondary data collection came from birth report. Data were analyzed using the chi-square test. Results: Based on results, it was shown that highest type of vaginal delivery was [85%], non-hepatitis B group, p-value 0.718. The highest condition of newborn is in normal category [95%], non-hepatitis B group, with a p-value of 0.553. The largest birth weight of babies was in the normal category, non-hepatitis B group [86.7%], p-value 0.129. In terms of indicators of postpartum haemorrhagia complications, the highest results were in the non-postpartum haemorrhagia category [91.6%], hepatitis B group, p-value 0.640. Conclusion: From the four indicators of birth outcomes, it was concluded that not has been significant correlation with the incidence of hepatitis B in pregnant women.